Effect of water-oil ratio on the photocatalytic performance of visible light-active BiVO4 nanoparticles prepared by inverse microemulsion-calcination method. (July 2022) - Huang, Jingyuan; Ma, Yueyong; Chen, Qianqian; Zhu, Jinyan; Jiang, Hongyi; Li, Hanliang; Yi, Lian; Li, Haiyan; Hong, Mei
Abstract: Nowadays, nano-photocatalysts (NPs) have become the research focus in the field of photocatalysis due to their excellent photocatalytic activity, and microemulsion is an effective method to prepare high-efficiency nano-photocatalysts. Here, BiVO4 NPs with high efficiency under visible light were prepared by a combination of reverse microemulsion method and calcination method. XRD, SEM, TEM, XPS, DRS, PL, BET and other characterization tests were used to comprehensively explore the influence of water-oil ratio on the physicochemical properties of the catalysts. The results show that BiVO4 NPs of monoclinic scheelite with high crystallization degree can be obtained by this method. The microscopic morphology, specific surface area and total pore volume of BiVO4 NPs are significantly affected by the water-oil ratio. It is difficult to obtain BiVO4 NPs with small particle size and uniform dispersion under the condition of too low or too high water-oil ratio. Meanwhile, the photogenerated carrier recombination efficiency of the catalyst is significantly improved, thus reducing the photocatalytic activity of the catalyst. Strikingly, the BiVO4 NPs obtained under the condition of water-oil ratio is 20 exhibited well-dispersed nanospheres with diameters ranging from 80 to 100 nm. It has the highest photocatalytic activity due to its high crystallinity, large specific surface area and total pore volume and relatively low photogenerated carrier recombination efficiency. Under visible light irradiation, the degradation efficiency of RhB can reach 97.69% in 100 min, and the rate constant is 0.03253 min −1 . Graphical abstract: Image 1 Highlights: Small-size BiVO4 catalysts were prepared by the inverse microemulsion - calcination method. The water-oil ratio have an important impact on the structural properties of the samples. Catalyst has the highest activity when water-oil ratio is 20. The degradation ratio and the rate constant of RhB reach to 97.69% and 0.03253 min −1 in 100 min severally. Because having small size structure, the largest specific surface area and so on.